DESKRIPSI KOMUNIKASI PERSUASIF DAN EFEKTIFITAS KERJA PEGAWAI PADA PERUSAHAAN JENANG MIRAH PONOROGO - Fikroh, Seviyenti (Dinamika Penelitian: Media Komunikasi Penelitian Sosial Keagamaan, 2021)
Jenang Mirah Company Ponorogo was produces Jenang. That’s company was founded in 1958 by Mr. Sastro Toesiman and his wife who live in the village of Josari, Jetis. This industry was initially founded on a small scale, with only a frying pan and other equipment. With this equipment, the production of Mirah jenang is increasing. Thanks to his hard work, in 1966 the company grew even bigger. So that in 1978 it reached the peak of its business, which in its marketing could reach to the Madiun, Malang, and Surabaya areas. This paper describes persuasive communication at the Mirah Ponorogo jenang company and provides an overview of the effectiveness of employees' work at the Mirah Ponorogo jenang company.